PENGARUH EMO DEMO TERHADAP PENGETAHUAN DAN SIKAP IBU SERTA KERAGAMAN MAKAN BALITA DI DESA LANGENSARI, BANTEN - Haryono, Shelse Gustima; Maulida, Nursyifa Rahma; Ashari, Chica Riska (Jurnal Gizi dan Pangan Soedirman, 2023)
Factors influencing stunting is complementary feeding practices which related to dietary diversity. Dietary Diversity has been documented as an indicator of adequate intake and associated with nutritional status. Nutrition education are needed to provide information through increase the knowledge, attitude, and feeding practices. Emotional demonstration (EMO-DEMO) as a participatory intervention approach in conveying information has become a purpose of the study to see the effect of intervention in Langensari Village, Banten. Pre-experimental with one group pre-post-test was a design of this study. The sample of respondent was 50 mothers who had a children aged 6-59 months. Simple random sampling was a technical method in collecting sample. The Wilcoxon Rank test was used to see the effect of knowledge, attitudes and feeding practices before and after the intervention. The result showed that there were a significant difference on knowledge, attitude, and feeding practices before and after intervention (p=0.000). Dietary Diversity Scores as an indicator of feeding practices found that there was an increase in the median score. Before the intervention, only 3 food groups were consumed by the children and became 4 food groups after the intervention. Emo demo has an effect on changes in knowledge, attitudes, and behaviour. This approach not only provides health related information, but also evokes the respondent’s feelings and emotions. So that, emo demo was encouraging them to change the behaviour especially on feeding practices with using dietary diversity scores.